What is Innovation in Higher Education? A conceptual approach (Innovaciones Educativas, 2024)
In higher education, educational innovation has become a widespread discourse as a key factor for quality education and as a response to the educational phenomena and trends brought about by globalization and the development of information and communication technologies (ICT) and digitalization.  Despite the relevance attributed to it, the concept is ambiguous and polysemic, as there is no clear social and academic consensus on its meaning. This paper aims to provide an insight into the concept of innovation, distinguishing between its general economic meaning and its notion and possible application in higher education, based on a conceptual framework that concludes with a discussion that seeks to answer the question: what does it mean to innovate in higher education? To achieve this, the levels of deepening, the dimensions of the approach and the implications of its application in Higher Education Institutions (HEI) are analyzed. The analysis concludes with a reflection on educational innovation in HEIs as an element that intervenes culturally, as it emerges from the symbolic field in a process that transforms the beliefs, values, and knowledge of the different members of the educational community. This goes beyond the introduction of ICT in educational practice since this requires an institutional vision with integral involvement.
Keywords: Innovative Behavior; Educational Change; Higher Education; Educational Innovation; Pedagogical Innovation